Synergistic enhancement of formic acid electro-oxidation on PtxCuy co-electrodeposited binary catalysts - Yaser M. Asal; Ahmad M. Mohammad; Sayed S. Abd El Rehim; Islam M. Al-Akraa (Journal of Saudi Chemical Society, 2022)
A propitious binary catalyst composed of Pt and Cu which were electrodeposited simultaneously onto a glassy carbon (GC) substrate was recommended for the formic acid (FA) electro-oxidation reaction (FAOR); the principal anodic reaction in the direct FA fuel cells (DFAFCs). The simultaneous co-electrodeposition of Pt and Cu in the catalyst provided an opportunity to tune the geometric functionality of the catalyst to resist the adsorption of poisoning CO at the Pt surface that represented the major impediment for DFAFCs marketing. The catalytic activity of the catalyst toward FAOR was significantly influenced by the (Pt4+/Cu2+) molar ratio of the electrolyte during electrodeposition, which also affected the surface coverage of Pt and Cu in the catalyst. Interestingly, with a molar (Pt4+/Cu2+) ratio of (1:4), the catalyst sustained superior (3.58 compared to 0.65 obtained at the pristine Pt/GC catalyst) activity for FAOR, concurrently with up to four-times (0.73 compared to 0.18 obtained at the pristine Pt/GC catalyst) improvement in the catalytic tolerance against CO poisoning. This associated, surprisingly, a negative shift of ca. 336 mV in the onset potential of FAOR, in an indication for the competitiveness of the catalyst to minimize superfluous polarizations in DFAFCs. Furthermore, it offered a better (ended up with 20% loss in the activity) stability for continuous (1 h) electrolysis than pristine Pt/GC catalyst (the loss reached 35%). The impedance and CO stripping measurements together excluded the electronic element but confirmed the geometrical influence in the catalytic enhancement.